Long-Term Effects of Androgen Deprivation Therapy on Cognitive Function in Prostate Cancer Patients - Asif, Muhammad; Patujo, Yassar Hussain; Shaikh, Abdul Ghaffar; Shahjehan, Shahjehan; Asghar, Hassan Raza; Shamsher, Mohammad Asad; Kousar, Iqra (Journal of Neonatal Surgery, 2025)
Background: Androgen deprivation therapy (ADT) remains foundational in managing advanced prostate cancer. Although quite successful at managing the progression of tumors, its impact on cognitive functioning over a prolonged period is concerning. This study sought to examine the association between ADT duration and cognitive performance among prostate cancer patients. Methods: A cross-sectional study was carried out between January 2023 and December 2024 with 71 prostate cancer patients on ADT. Participants were categorized into two groups based on duration of therapy: less than 2 years, and 2 years or more. Cognitive domains were assessed using MMSE, MoCA, HVLT, Trail Making B Test and Clock Drawing test. Other Depressive symptoms, fatigue, and quality of life were also measured. ‘Data analysis was conducted with SPSS v25 with significance set at p < 0.05’. Results: Patients on long-term ADT exhibited significantly lower scores in global cognition, memory, executive functioning, and visuospatial tasks compared to those on short-term therapy. Mean MMSE and MoCA scores were lower in the long-term group (26.4 vs. 27.9 and 22.1 vs. 24.2, respectively). Depression scores and fatigue levels were higher, while quality of life was significantly reduced in patients receiving ADT for two years or more. Conclusion: Prolonged ADT use in prostate cancer patients is associated with a decline in cognitive performance and psychosocial well-being. These findings support the need for cognitive monitoring and multidisciplinary support during long-term hormone therapy.